Experimental Analysis of Low Voltage Arc Between Carbon Electrodes with Unknown Cores - Šimek, David (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2016)
The paper is focused on an electric arc spectroscopy diagnostics related to electric low voltage apparatuses. Measurement of radiation spectra of the electric arc burning between carbon electrodes with unknown cores is presented. Measured radiation spectrum has a lot of suitable atomic spectra lines for comparison purposes. The problems connected with the measurements are discussed. The main part of the paper deals with a prediction of composition of the measured arc plasma. Atomic lines database of National Institute of Standards and Technology was used as a spectral data source for the calculations.
Keywords: switching arc; arc plasma composition; atomic emission spectroscopy